2013
DOI: 10.1095/biolreprod.112.106914
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Reduces the Primordial Follicle Pool in the Bovine Ovarian Cortex Ex Vivo and in the Murine Ovary In Vivo1

Abstract: Infections of the uterus or mammary gland with Gram-negative bacteria cause infertility in cattle, not only during disease but also for some time afterward. Even though these infections are in organs distant from the ovary, metritis and mastitis perturb antral follicle development and function in vivo. Although granulosa cells from antral follicles express toll-like receptor 4 (TLR4), and detect and mount an inflammatory response to lipopolysaccharide (LPS) from Gram-negative bacteria, it is not known whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 43 publications
3
70
1
1
Order By: Relevance
“…However, the reason for this susceptibility is unclear. It is worth noting that other studies have shown functional impairment of small follicles and enclosed oocytes associated with exposure to various inflammatory agents [57,90,91].…”
Section: Effect Of Mastitis On the Oocytementioning
confidence: 95%
“…However, the reason for this susceptibility is unclear. It is worth noting that other studies have shown functional impairment of small follicles and enclosed oocytes associated with exposure to various inflammatory agents [57,90,91].…”
Section: Effect Of Mastitis On the Oocytementioning
confidence: 95%
“…This suggests that for both the neonates and prepubescent rats, LPS was associated with a reduction in the number of primordial follicles. It was recently found that LPS reduces primordial follicle pool ex vivo in bovine ovarian cortex and in vivo in the murine ovary (Bromfield and Sheldon 2013). This reduction was associated with increased turnover of primordial follicles in bovine ovary, but it was associated with follicular atresia in mice (Bromfield and Sheldon 2013).…”
Section: A Single Lps Injection Was Sufficient To Reduce Primordial Fmentioning
confidence: 97%
“…These studies provide evidence for localized effects of LPS in the ovary. Indeed, in vitro LPS has been shown to disrupt granulosa cell oestradiol secretion via reduced expression of aromatase enzyme expression (Herath et al, 2007) and acute exposure to LPS increases follicular atresia and reduces the primordial ovarian follicle pool (Bromfield and Sheldon, 2013).…”
Section: Postpartum Uterine Healthmentioning
confidence: 99%